Igreja de Nossa Senhora do Rosário dos Pretos em Natal : religião (com) tradição e modernidade - Cavalcanti Júnior, Davi Alves (2021)
Modernity brought countless ways to experience the religious phenomenon and one of them can be seen in the search for the return of tradition. This phenomenon can be observed among traditional Catholics from the Church of Nossa Senhora do Rosário dos Pretos in the city of Natal-RN, who weekly participate in the Mass in the extraordinary form of the Roman Rite or as it is better known as Tridentine Mass. This practice demonstrates the desire of this group for the return of the Catholic tradition even in a period marked by profound changes in the Brazilian religious field. In this sense, this work has as main objective to analyze the relationship between religion and modernity through the meeting between the traditional and the contemporary, considering mainly the conceptual contributions of the French sociologist Danièle Hervieu-Léger (2008) in her work O Peregrino e o Converted: religion in motion and British sociologist Anthony Giddens (1991) in his work The consequences of modernity and the uncontrolled world, which help to understand the construction of new practical and theoretical paths.